Sex-specific features of spine densities in the hippocampus - Brandt, Nicola; Löffler, Tobias; Fester, Lars; Rune, Gabriele M. (Scientific Reports, 2020)
Previously, we found that in dissociated hippocampal cultures the proportion of large spines (head diameter ≥ 0.6 μm) was larger in cultures from female than from male animals. In order to rule out that this result is an in vitro phenomenon, we analyzed the density of large spines in fixed hippocampal vibratome sections of Thy1-GFP mice, in which GFP is expressed only in subpopulations of neurons. We compared spine numbers of the four estrus cycle stages in females with those of male mice. Remarkably, total spine numbers did not vary during the estrus cycle, while estrus cyclicity was evident regarding the number of large spines and was highest during diestrus, when estradiol levels start to rise. The average total spine number in females was identical with the spine number in male animals. The density of large spines, however, was significantly lower in male than in female animals in each stage of the estrus cycle. Interestingly, the number of spine apparatuses, a typical feature of large spines, did not differ between the sexes. Accordingly, NMDA-R1 and NMDA-R2A/B expression were lower in the hippocampus and in postsynaptic density fractions of adult male animals than in those of female animals. This difference could already be observed at birth for NMDA-R1, but not for NMDA-R2A/B expression. In dissociated embryonic hippocampal cultures, no difference was seen after 21 days in culture, while the difference was evident in postnatal cultures. Our data indicate that hippocampal neurons are differentiated in a sex-dependent manner, this differentiation being likely to develop during the perinatal period.
CRIS-Team Scopus Importer:2020-07-24